(untitled) - McCord, Paul M. (Hoboken, N.J., 2007)
In Creating a Million-Dollar-a-Year Sales Income, Paul McCord sets out a detailed, yet flexible course of action that has been proven to generate referrals in virtually any sales system or environment and in any industry. This easy-to-read reference guide features compelling real-world examples of common mistakes and solutions that will transform lost opportunities into real prospects. Create the referral base that guarantees success!
Keywords: Selling,Business referrals,Bán hàng,Kinh doanh